PENGARUH DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA SEKOLAH DASAR PADA MATERI PERPINDAHAN ENERGI PANAS - Yuliawati, Neng; Panjaitan, Regina Lichteria; Maulana, Maulana (Jurnal Pena Ilmiah, 2017)
The ability of think creatively can be used to solve problems in real life. The purpose of this research is to know the impact of discovery learning onÂ creative thinking ability on high, medium and low group students. Teaching method on this research is discovery learning. This research uses pre-experimental method with one-group pretest and posttest design. The population that used on this study is all 4th grade students in Tanjungsari, Sumedang. The samples that studied are 4th grade students of SDN Sukamantri and SDN Cikandang. The instruments thas used are creative thinking ability test, teacher performance observation, and student activity, questionnaire, note field and interviews. Based on the reasults, discovery learning can improve creative thinking ability of high, medium and low group students. Other than that, thereâ€™s no enhancement differences between high, medium and low group students.Â